Multi-project wafer runs for electronic graphene devices in the European 2D-Experimental Pilot Line project - Bárbara Canto; Martin Otto; Arantxa Maestre; Alba Centeno; Amaia Zurutuza; Bianca Robertz; Eros Reato; Bartos Chmielak; Stefanie L. Stoll; Andreas Hemmetter; Florian Schlachter; Lisa Ehlert; et al. (Nature Communications)
Abstract The commercialization of electronic devices based on graphene has not yet been successful, even 20 years after its first isolation. To this end, the European Commission is supporting research toward establishing a European experimental pilot line for electronic and optoelectronic devices based on graphene and related two-dimensional (2D) materials, namely the Experimental Pilot Line (2D-EPL) project. Here, we report the results obtained during the first and third multi-project wafer (MPW) runs completed at the end of 2022 (MPW run 1) and 2023 (MPW run 3) as an outcome of the 2D-EPL. Test devices were measured across the wafers to assess the device quality and variability before delivering the fabricated dies to the customers. Raman spectroscopy confirmed minimal structural changes in the graphene caused by the fabrication process, while electrical measurements of two different device types verified the device specifications defined in the process design kit.